2017
DOI: 10.1515/orhu-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

The cranial morphometrics of the wildfowl (Anatidae)

Abstract: Wildfowl (Anatidae) are a diverse group of birds and globally distributed. These birds feed by widely varying methods, there are generalist and specialist species. In a number of vertebrate taxa trophic specializations have led to distinct differences in the morphology of the skull, like in birds. Our knowledge and understanding of the relationship between cranial morphology and feeding mechanism of wildfowl are limited. The aim of this article is to increase our knowledge of the relationship between skull sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Various studies on habitat use by community of ducks showed separation of niches between species in horizontal dimensions, such as size of wetlands, vegetation characteristics, and chemical characteristics of water (Bengston 1971, Weller 1975, Toft et al 1982, Anderson & Ohmart 1988, Monda & Ratti 1988, Bergan & Smith 1989, Nummi & Poysa 1993, Nudds et al 1994. Ferruginous Duck is belonging to the omnivore diving ducks according to diet composition and feeding methods (Pecsics et al 2017). Some studies demonstrate the presence of vertical partitioning in foraging methods in the depths of water column.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies on habitat use by community of ducks showed separation of niches between species in horizontal dimensions, such as size of wetlands, vegetation characteristics, and chemical characteristics of water (Bengston 1971, Weller 1975, Toft et al 1982, Anderson & Ohmart 1988, Monda & Ratti 1988, Bergan & Smith 1989, Nummi & Poysa 1993, Nudds et al 1994. Ferruginous Duck is belonging to the omnivore diving ducks according to diet composition and feeding methods (Pecsics et al 2017). Some studies demonstrate the presence of vertical partitioning in foraging methods in the depths of water column.…”
Section: Discussionmentioning
confidence: 99%
“…As Pecsics et al (2017) found that some cranial measures are related to the feeding method, the variation of the lacrimal with regard to the rest of the skull makes possible to use this structure for species identification (Ellrott & Schmitz, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The morphotypes do not match exactly groups based on ecology or habits. For example, Pecsics, Laczi, Nagy, and Csörgő (2017) clusters anatids in six groups by feeding methods: grubbing, grazing, dabbling, upending, diving and pursuit diving. Taxa of the three morphotypes can be classified as grubbers or grazers ( Chauna , Branta , Chloephaga ), or as divers ( Biziura , Oxyura , Somateria ), dabblers and upending feeders can be found in Types II and III ( Cygnus , Lophonetta ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation of cranial morphology is analysed using landmark-based geometric morphometry. In our former study, we used conventional morphometric variables which were selected a priori (Pecsics et al 2017), however in this case the meaningful variables are discovered by the analysis presented in a more recent study (Pecsics et al 2018). We should not choose them before the analysis.…”
Section: Landmarks and Proceduresmentioning
confidence: 99%